The Role Of Information Technology In Enhancing Performance Evaluation And Responsibility Accounting (Empirical Study In Jordan Hotels ) - محمد, صفاء احمد; محمد, سليمان حسين (Journal of Economics and Administrative Sciences, 2012)
This paper suggesting a new modern method to evaluate the performance of hotel industry at Jordan instead of the classical method used by the industry and that is Bench Marking , this method can be done by comparing the performance of hotel industry at two serial years which helps in calculating a standard performance .  The industry can use this standard to identify the variance, which make the evaluation of performance easier and support the efforts to develop the hotel industry at all levels and enable to give high quality services to customers.     The study believed that this situation would not be achieved unless the hotel industry will apply and use an applicable Information Technology, which supply the necessary data to calculate the mentioned standard.          The study selected the services sector to achieve its objectives and five stars Hotels selected as purposive sample which was located at five different area (regions) in Jordan, These hotels are : Amman , Aqaba , Al- Petra ,WadiMousa and Dead See, this will help the study to evaluate the performance of Hotel industry at different geographic areas .